2020
DOI: 10.5897/ajbm2019.8885
|View full text |Cite
|
Sign up to set email alerts
|

How universities fill the talent gap: The data scientist in the Italian case

Abstract: This research paper explores Italian study programs in data science in order to verify if knowledge and skills developed during the universities' path are fit with data scientist job demand. The issue is introduced considering the companies' growing need to derive insights from data, and consequently, to search for a staff with analytical expertise, the so-called data scientists quite rare. Literature review is focused on the data scientist's specific characteristics. According to the ideal profile, the data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The results obtained in this research allow us to conclude that employers require that their employees know, understand and know how to apply mathematical skills in the finance area of their company: use math to solve basic financial budgeting problems, understand math calculations to solve financial interest calculation problems, and apply math skills to solve complicated financial problems such as the effect of inflation and making investment plans. These results are consistent with [26] and [23]. They identified the math ability as one of the top ten skills managers and business leaders have to have.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results obtained in this research allow us to conclude that employers require that their employees know, understand and know how to apply mathematical skills in the finance area of their company: use math to solve basic financial budgeting problems, understand math calculations to solve financial interest calculation problems, and apply math skills to solve complicated financial problems such as the effect of inflation and making investment plans. These results are consistent with [26] and [23]. They identified the math ability as one of the top ten skills managers and business leaders have to have.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of [20] who showed that the mathematical discipline has links with technology knowledge. Currently, companies need the employee to have interdisciplinary knowledge [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations